2016
DOI: 10.1016/j.jtho.2016.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pemetrexed-Based Chemotherapy in Patients with ROS1 Fusion–Positive Lung Adenocarcinoma Compared with in Patients Harboring Other Driver Mutations in East Asian Populations

Abstract: ROS1 fusion positivity is probably a favorable factor of pemetrexed-based therapy for patients with lung adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
50
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 48 publications
4
50
0
1
Order By: Relevance
“…Chen et al . reported that PEM‐based chemotherapy was effective in NSCLC patients with EGFR mutation, ALK fusion, and ROS 1 rearrangement (overall response rates: 25.5%, 28.1%, and 57.9%, respectively) . Our case also indicated the effectiveness of pemetrexed‐based chemotherapy for NSCLC with a MET exon 14 skipping mutation.…”
Section: Discussionsupporting
confidence: 61%
“…Chen et al . reported that PEM‐based chemotherapy was effective in NSCLC patients with EGFR mutation, ALK fusion, and ROS 1 rearrangement (overall response rates: 25.5%, 28.1%, and 57.9%, respectively) . Our case also indicated the effectiveness of pemetrexed‐based chemotherapy for NSCLC with a MET exon 14 skipping mutation.…”
Section: Discussionsupporting
confidence: 61%
“…We found that the PFS of patients who treated with pemetrexed-based chemotherapy was 179 days, which was shorter than that in a European prior retrospective study (7.2 months) [14], or in a recently published retrospective study (7.5 months) which was carried out in Taiwan [16]. The difference can be triggered by the study population, tumor heterogeneity and previous treatments of patients.…”
Section: Discussionmentioning
confidence: 63%
“…28,38,41 Lung adenocarcinoma with the ROS1 fusion gene has been reported to be highly responsive to crizotinib or pemetrexed. 5,[42][43][44] However, the current study enrolled a small number of patients, and the effectiveness of both drugs was not obvious in these patients.…”
Section: Discussionmentioning
confidence: 80%